The Stil protein regulates centrosome integrity and mitosis through suppression of Chfr - Castiel, Asher; Danieli, Michal Mark; David, Ahuvit; Moshkovitz, Sharon; Aplan, Peter D.; Kirsch, Ilan R.; Brandeis, Michael; Krämer, Alwin; Izraeli, Shai (Journal of cell science, 2011)
Stil (Sil, SCL/TAL1 interrupting locus) is a cytosolic and centrosomal protein expressed in proliferating cells that is required for mouse and zebrafish neural development and is mutated in familial microcephaly. Recently the Drosophila melanogaster ortholog of Stil was found to be important for centriole duplication. Consistent with this finding, we report here that mouse embryonic fibroblasts lacking Stil are characterized by slow growth, low mitotic index and absence of clear centrosomes. We hypothesized that Stil regulates mitosis through the tumor suppressor Chfr, an E3 ligase that blocks mitotic entry in response to mitotic stress. Mouse fibroblasts lacking Stil by genomic or RNA interference approaches, as well as E9.5 Stil−/− embryos, express high levels of the Chfr protein and reduced levels of the Chfr substrate Plk1. Exogenous expression of Stil, knockdown of Chfr or overexpression of Plk1 reverse the abnormal mitotic phenotypes of fibroblasts lacking Stil. We further demonstrate that Stil increases Chfr auto-ubiquitination and reduces its protein stability. Thus, Stil is required for centrosome organization, entry into mitosis and cell proliferation, and these functions are at least partially mediated by Chfr and its targets. This is the first identification of a negative regulator of the Chfr mitotic checkpoint.
Gesehen am 28.06.2022